Biomass Carbon Stocks and Fluxes in States and Union Territories of India - Iqbal, Kaiser; Pala, Nazir A.; Bhat, Jahangeer A.; Hussain, Aatif; Banday, Muneesa; Negi, A. K. (Indian Forester, 2020)
Studies to assess carbon stocks and their potential for implementation of REDD and REDD+ projects and policies have been conducted by scientists, academicians and policy makers all over the world. The present study reports estimates of carbon pools and fluxes in forests of all Indian states and Union Territories since 2003 to 2017. To estimate the carbon storage in state wise in forests growing stock data from 2003 to 2017 were used. Biomass data for the years 2003, 2009, 2011, 2013, 2015 and 2017 were used to calculate the net flux caused by deforestation and degradation, between five assessment periods i.e., Assessment Period first (ASP I; 2003-2009), (ASP II; 2009-2011), (ASP III; 2011-2013), (ASP IV; 2013-2015) and (ASP V; 2015-2017). The estimated carbon stock (Mt) was 2912.14, 2768.87, 2745.69, 2569.01, 2618.84 and 2643.64 Mt respectively for the years 2003, 2009, 2011, 2013, 2015 and 2017. There was a net positive flux for first three assessment periods (698.04 Mt of CO2 in ASP I, 85.08 Mt of CO2 in ASP II, 648.4 Mt of CO2 in ASP III) and net negative flux (-184.14 Mt of CO2 in ASP IV and -91.00 Mt of CO2 in ASP V) for last two assessment 22 periods. The net flux also impacted annual CO2 emission and was of the 2 value of 349.02, 42.54, 324.2, -92.07 and -45.50 Mt of CO2 respectively for respective assessment periods. The carbon stock in India's forest biomass decreased continuously from 2003 onwards till 2015 thereafter; there is an increase in carbon stock from 2569.01 in 2015 to 2643.64 in 2017. Further forest degradation will reduce forest carbon density and hence release of carbon into the atmosphere will enhance leading to global warming. However, proper management of degraded forests and ways to enhance the forest cover will result in significant increase in carbon sequestration by India's forests and may have more scope during implementation of REDD and REDD+ projects and policies.